Efficacy and safety of temperature‐controlled intraductal radiofrequency ablation in advanced malignant hilar biliary obstruction: A pilot multicenter randomized comparative trial. (4th December 2021) - Kang, Huapyong; Han, Sung Yong; Cho, Jae Hee; Kim, Eui Joo; Kim, Dong Uk; Yang, Jae Kook; Jeon, Soyoung; Park, Goeun; Lee, Tae Hoon
Abstract: Purpose: We aimed to evaluate the efficacy and safety of temperature‐controlled intraductal radiofrequency ablation (ID‐RFA) for advanced malignant hilar biliary obstruction (MHBO). Methods: Patients were randomly assigned to RFA group (ID‐RFA and bilateral plastic stent [PS]) or non‐RFA group (bilateral PS) at a 1:1 ratio. Exchange to self‐expanding metal stent (SEMS) was performed after 3 months or when premature PS occlusion occurred. Total event‐free stent patency, overall survival (OS), and adverse events (AEs) were analyzed. Results: A total of 30 patients from three hospitals were enrolled. Stent patency and OS did not differ between the two groups (178 days vs 122 days, P  = .154; 230 days vs 144 days, P  = .643; respectively). In patients with each stricture length ≥11 mm on both sides, stent patency was longer in the RFA group than in the non‐RFA group (175 days vs 121 days, P  = .028). More patients received elective exchange to SEMS without PS occlusion in the RFA group than in the non‐RFA group (69.2% vs 23.1%, P  = .018). AE rates did not differ between the two groups. Conclusions: Temperature‐controlled ID‐RFA for advanced MHBO was safe and feasible. It could prevent premature PS occlusion within 3 months. Abstract : Kang and colleagues conducted a pilot randomized controlled trial comparing temperature‐controlled intraductal radiofrequency ablation plus stent placement with stent placement alone in advanced malignant hilar obstruction. Intraductal radiofrequency ablation was safe and feasible, resulted in a lower rate of premature stent occlusion, and may help patients receive scheduled stent exchange.